Analysis of Body Posture and Mental Workload in Production Operators Using the Rapit Entire Body Assesment and Modifiet Cooper Harper Methods - Boy Isma Putra; Prayoga Dwi Firmansyah (INOVTEK Polbeng - Seri Informatika, 2024)
Muscle fatigue can cause problems or musical symptoms. The problem of musculoskeletal can be affected by such factors as energy, posture, action over and over - again, and longer working hours, with a 20% delay production percentage. It aims to analyze the body posture and mental workload on the production operator. The study's sample removal was made of 15 production operators at the XYZ corporation. The purpose of the study is, to know the impact of body posture, evaluate the risk factors of less-ergonomic working posture, and know the category of mental workload experienced by production operators at the XYZ pt. The data analysis techniques used in this study are Reba and MCH analysis. Research results by using the Reba method score 7 which means moderate risk work if carried on a long period, and changes need to be made immediately. On MCH methods obtained underload job classifications on purging and refining activities, installment of the plate, end of the plate, final fitting, casting, finishing, shipping, release of the product, PC strand cutting, and removal of the product. Whereas an optimum classification load on the scrounging activities section. Overload classification is the installation, spiral, and PC strand, and early 20% stress.